The structure of the human zeta-globin gene and a closely linked, nearly identical pseudogene. - Proudfoot, N; Gil, A; Maniatis, T (1982)
DNA sequencing studies indicate that only one of two closely linked human embryonic alpha-like globin genes, zeta (zeta), encodes a functional polypeptide. The other is a pseudogene (psi zeta) that differs by only 3 bp in the protein coding sequence, one of which converts the codon for amino acid 6 into a chain termination codon. Both zeta-globin genes differ from all other alpha-like genes thus far reported in that they contain large introns consisting, in part, of simple repeat sequences. Intron 1 of each gene contains a variation of the repeat sequence ACAGTGGGGAGGGG, while intron 2 contains the repeat sequence CGGGG. Comparison of the human zeta- and alpha-globin gene sequences reveals that the embryonic and adult alpha-like genes began to diverge from each other relatively early in vertebrate evolution (400 million years ago). In contrast, the beta-like embryonic globin gene, epsilon (epsilon), is the product of a much more recent evolutionary event (200 million years ago). Thus, even though the temporal and quantitative expression of zeta- and epsilon-globin genes must be coordinately controlled during development, their evolutionary histories are clearly distinct.